2005
DOI: 10.1111/j.1746-1561.2005.tb06657.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Nutrition Education Program on the Dietary Behavior and Nutrition Knowledge of Second-Grade and Third-Grade Students

Abstract: This research investigated the effects of a nutrition education program on dietary behavior and nutrition knowledge among elementary school-aged children participating in a Social Cognitive Theory-based nutrition education program. Participants included 1100 second-grade and third-grade students selected by convenience-type sampling from public schools in Alabama. A preassessment and postassessment control group design assessed dietary behavior and nutrition knowledge using Pizza Please, a specially designed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 16 publications
4
58
0
4
Order By: Relevance
“…The present review summarises sixteen papers describing fourteen interventions published between years 1990 and 2010, conducted mainly in the USA (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) , one in South America (42) and three in Europe (43)(44)(45) . Children's age spanned from 5 to 12 years, and with the exception of one study that recruited girl scouts only (35) , all studies targeted both girls and boys.…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present review summarises sixteen papers describing fourteen interventions published between years 1990 and 2010, conducted mainly in the USA (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) , one in South America (42) and three in Europe (43)(44)(45) . Children's age spanned from 5 to 12 years, and with the exception of one study that recruited girl scouts only (35) , all studies targeted both girls and boys.…”
Section: Study Descriptionmentioning
confidence: 99%
“…None of the lower intensity studies were individualised, instead utilising either group education (30,40) or environmental strategies (e.g. provision of milk as part of school lunch programme (44) ).…”
Section: Intervention Intensitymentioning
confidence: 99%
“…유아의 식습관은 가정에서부터 형성되며, 부모로부터 가장 많은 영 향을 받는다 (An and Im, 1994;Gillespie, 1981;Nelms, 1997;Powers et al, 2005). 그러므로 유아의 식습관 개선을 위해 서는 부모의 지속적인 관심과 참여가 함께 이루어져야만 효 과를 볼 수 있다 (Moon, 1991).…”
unclassified
“…Increase of nutritional knowledge in the control group could be due to routine educational programs at schools. Other studies have shown that nutrition education interventions could increase nutritional knowledge (13,21), which is a necessary but not sufficient factor for improving food behaviors (22). Some studies have reported that children's nutritional behaviors are not related to their nutritional knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Schools are recognized as proper places for nutritional and behavioral interventions because children spend most of their time there (10). Results of nutrition education program in other countries have shown that it could improve nutrition knowledge and dietary habits among the children (11)(12)(13). Here, we decided to assess the effect of a school-based nutrition education program on the nutritional status of grade four primary school students in Shiraz, Iran.…”
mentioning
confidence: 99%